Integrating career education into foreign language programmes in the context of new liberal arts in China: an integrative model / Shikun Shan, Supramaniam Kaarthiyainy and Mohammad Nor Afandi Ibrahim - Shan, Shikun; Supramaniam, Kaarthiyainy; Ibrahim, Mohammad Nor Afandi (Universiti Teknologi MARA, 2025)
Amidst the ongoing new liberal arts education reform in China, foreign language programmes encounter both challenges and opportunities. Traditionally, foreign language education has emphasized linguistic skills, and yet overlooked the development of professional qualities and employability, thus leading to low rate of graduate employment, reduction of the enrollment scale or even cancellation of foreign language programmes. In response, this study proposed a holistic model that integrates career education into foreign language programmes targeted for improving students’ professional competence and employment competitiveness. The researchers selected the integration in Shandong Jianzhu University as a case study in which questionnaire survey responses were collected from the faculty leaders and teachers, alumni, students, parents, employers and education experts, and Analytic Hierarchy Process and contrast analysis were utilized to analyse the effect of career education integration. The findings showed that the cultivation process is valued as the most important factor followed by teaching effectiveness and that not only the employment rate of graduates and also the ratio of high-quality employment have increased. It has been tested that this new integration model is fruitful in promoting the development of foreign language programmes and offers new theoretical support and practical guidance for the revitalization of foreign language programmes.